Hid, Rpr and Grim negatively regulate DIAP1 levels through distinct mechanisms. - Yoo, S.J.; Huh, J.R.; Muro, I.; Yu, H.; Wang, L.; Wang, S.L.; Feldman, R.M.; Clem, R.J.; Muller, H.A.; Hay, B.A. (Nature Cell Biology, 2002)
Inhibitor of apoptosis (IAP) proteins suppress apoptosis and inhibit caspases. Several IAPs also function as ubiquitin-protein ligases. Regulators of IAP auto-ubiquitination, and thus IAP levels, have yet to be identified. Here we show that Head involution defective (Hid), Reaper (Rpr) and Grim downregulate Drosophila melanogaster IAP1 (DIAP) protein levels. Hid stimulates DIAP1 polyubiquitination and degradation. In contrast to Hid, Rpr and Grim can downregulate DIAP1 through mechanisms that do not require DIAP1 function as a ubiquitin-protein ligase. Observations with Grim suggest that one mechanism by which these proteins produce a relative decrease in DIAP1 levels is to promote a general suppression of protein translation. These observations define two mechanisms through which DIAP1 ubiquitination controls cell death: first, increased ubiquitination promotes degradation directly; second, a decrease in global protein synthesis results in a differential loss of short-lived proteins such as DIAP1. Because loss of DIAP1 is sufficient to promote caspase activation, these mechanisms should promote apoptosis.